FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK PADA PENGUSAHA DI PASAR ATOM SURABAYA - Christian, Denny; Shanti, Shanti; Irawan, Ronny (Jurnal Akuntansi Kontemporer, 2015)
Countries need a many of funds to maintain the country and development the country. One source of funds for the government’s is a tax revenue. A very important thing in tax revenue is a willingness to pay taxes by the tax payers. But the fact is a tax levy by the government is much less than payments made by the taxpayer, this is due to the presence of obstacles, principles of taxation, namely the result of the indirect tax collections are enjoyed by taxpayer. One of the city's icon of Surabaya is Pasar Atom Surabaya where is a market many entrepreneurs open businesses and the number of visitors who flock to the entertainment venues. This is potentially a tax receipt for your country or region. The purpose of this research is to test a factor that influenced the willingness to pay taxes of entre-preneurs in Pasar Atom Surabaya. Tax paying awareness, knowledge and understanding will be taxation, the effectiveness of the tax system, and the level of confidence in the Government and legal system is the independent variable. The object of the research was a entrepreneurs in the Pasar Atom Surabaya that listed in PT. Prosam Plano. The data source is obtained by dividing the questionnaire directly to business owners, and data analysis techniques using multiple linear regression. The results of this research showed that the effectiveness of the tax system which only affect willingness to pay taxes significantly to entrepreneurs in the Pasar Atom Surabaya. While the tax paying awareness factor, knowledge and an understanding of the rules of taxation, and the level of confidence in the sys-tem of Government and laws have no effect significantly to willingness to pay taxes by employers in the Pasar Atom Surabaya.